PENGARUH KAUSALITAS EKSPOR, IMPOR, DAN GDP DI INDONESIA - Larasati Indramadhini; Poltak P Sitompul (Media Ekonomi, 2015)
This thesis is discussing about the analysis of causality or reciprocity that happen between export, import and GDP in Indonesia 1983-2013. The variable which used are export, import and GDP in Indonesia. The method which used in this thesis is Vector Autoregression (VAR) method and Granger Causality Test. The purpose of this research is to determine the influence of causality of export and GDP, import and GDP, and also export and import. Based on the result of Granger Causality Test, export can influence GDP, import can influence GDP and export can influence import. Based on Johansen Cointegration Test, all of the variables only have a causal relationship in the short term. In the result of using this VAR method, show that in Indonesia, based on the three models which test by akaike value the lowest is import model, so it can conclude that the best model for Indonesia is Import=f (GDP, export).